2021
DOI: 10.3748/wjg.v27.i40.6874
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided vascular interventions: Current insights and emerging techniques

Abstract: Endoscopic ultrasound (EUS) is one of the significant breakthroughs in the field of advanced endoscopy. In the last two decades, EUS has evolved from a diagnostic tool to a real-time therapeutic modality. The luminal gastrointestinal (GI) tract provides a unique opportunity to access multiple vascular structures, especially in the mediastinum and abdomen, thus permitting a variety of EUS-guided vascular interventions. The addition of the doppler and contrast-enhanced capability to EUS has further helped provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Due to the detrimental high rupture risks of up to 20%, allow for EUS-guided therapy to be an effective option for patients[ 40 ]. Many case-reports and series outlined good outcomes with obliteration of pseudoaneurysm following EUS-guided treatment, as reported by Mann et al [ 27 ], in a recent review of the literature. Recently, one study by Rai et al [ 41 ], aimed to study EUS-guided glue and coil injection in six patients who failed angiographic embolization of splenic artery pseudoaneurysm.…”
Section: Pseudoaneurysm Embolizationmentioning
confidence: 75%
See 3 more Smart Citations
“…Due to the detrimental high rupture risks of up to 20%, allow for EUS-guided therapy to be an effective option for patients[ 40 ]. Many case-reports and series outlined good outcomes with obliteration of pseudoaneurysm following EUS-guided treatment, as reported by Mann et al [ 27 ], in a recent review of the literature. Recently, one study by Rai et al [ 41 ], aimed to study EUS-guided glue and coil injection in six patients who failed angiographic embolization of splenic artery pseudoaneurysm.…”
Section: Pseudoaneurysm Embolizationmentioning
confidence: 75%
“…The study concluded the use of EVL to be limited to collaterals running parallel to the varices whilst sclerotherapy to be used for paraesophageal veins with a larger diameter and a perforation pattern[ 18 ]. Furthermore, the utilization of EUS technology provided effective directed treatment option of pattern types that aided a successful clinical outcome[ 27 ]. Moreover, in one study that utilized a sclerosing agent targeted under EUS guidance, an average of 2 to 3 sessions required to achieve complete obliteration.…”
Section: Esophageal Varicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, derived from the same concept and safety profile as islet cell transplantation by interventional radiology using Doppler imaging guidance, in which the portal vein is accessed percutaneously, emerging reports have centered on sampling and investigating portal blood in patients with PDAC. Recently, the utility of EUS-guided vascular access of the portal vein for diagnostic and therapeutic interventions has been evaluated with a satisfactory safety profile [ 23 ].…”
Section: Discussionmentioning
confidence: 99%